2018
DOI: 10.1111/cdev.13086
|View full text |Cite
|
Sign up to set email alerts
|

Infant Motor Development in Autism Spectrum Disorder: A Synthesis and Meta‐analysis

Abstract: Studies of infant motor development in autism spectrum disorder (ASD) have increased in recent years. This article synthesized this literature through meta-analysis to assess (a) whether infant motor ability differs in ASD relative to neurotypical controls; and (b) whether motor ability and communication are related in infants with ASD. Study 1 aggregated data from 1,953 infants with ASD (ages 3.0-42.0 months), and Study 2 included 890 infants with ASD (age 6.0-42.9 months). Study 1 revealed that infant motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 80 publications
4
53
1
1
Order By: Relevance
“…Doing so is important for two reasons. First, learning to sit supports the development of object exploration (e.g., Marcinowski et al, 2019;Rochat & Goubet, 1995;Soska & Adolph, 2014); Second, HR infants as a group begin to sit later than their LR peers, and this transition may unfold differently for them (e.g., Leezenbaum & Iverson, 2019;Nickel et al, 2013;West, 2018). Our data revealed that all infants-regardless of risk status-demonstrated changes in object exploration behavior as they transitioned from novice to experienced sitting.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Doing so is important for two reasons. First, learning to sit supports the development of object exploration (e.g., Marcinowski et al, 2019;Rochat & Goubet, 1995;Soska & Adolph, 2014); Second, HR infants as a group begin to sit later than their LR peers, and this transition may unfold differently for them (e.g., Leezenbaum & Iverson, 2019;Nickel et al, 2013;West, 2018). Our data revealed that all infants-regardless of risk status-demonstrated changes in object exploration behavior as they transitioned from novice to experienced sitting.…”
Section: Discussionmentioning
confidence: 59%
“…Growing evidence indicates that motor development is delayed among infants who are at heightened risk (HR) for developing autism spectrum disorder (ASD) by virtue of having an affected older sibling (e.g., Garrido, Petrova, Watson, Garcia-Retamero, & Carballo, 2017;Ozonoff et al, 2011;West, 2018). Indeed, both sitting and object exploration skills may be affected.…”
Section: Introductionmentioning
confidence: 99%
“…This may account for the relatively poorer locomotor quotients corresponding with an increasing age in the present study. Some prospective follow-up studies of high-risk infants across early development have found that motor difficulties in the infancy period is associated with later ASD diagnosis or ASD symptoms ( Estes et al, 2015 ; Paquet et al, 2016 ; West, 2019 ). Therefore, motor difficulties may be an early marker preceding a diagnosis of ASD, but longitudinal follow-up studies are needed for further verification.…”
Section: Discussionmentioning
confidence: 99%
“…Reindal et al reported a mean AOW of 15.3 months ±5.5 in children with ASD versus 14.1 months ± 3.4. AOW is reported to be later in autism spectrum disorder (ASD) compared with typical normal development [44].…”
Section: Discussionmentioning
confidence: 99%